2020
DOI: 10.1609/aaai.v34i07.6615
|View full text |Cite
|
Sign up to set email alerts
|

PsyNet: Self-Supervised Approach to Object Localization Using Point Symmetric Transformation

Abstract: Existing co-localization techniques significantly lose performance over weakly or fully supervised methods in accuracy and inference time. In this paper, we overcome common drawbacks of co-localization techniques by utilizing self-supervised learning approach. The major technical contributions of the proposed method are two-fold. 1) We devise a new geometric transformation, namely point symmetric transformation and utilize its parameters as an artificial label for self-supervised learning. This new transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…Other methods use technique such as CAM or analogous techniques [15,19,28,81,85,111] as a form of weakly supervised saliency or localisation maps. Recent works have suggested that saliency methods can also be applied to self-supervised networks [13,35], e.g. for object colocalisation [13].…”
Section: Related Workmentioning
confidence: 99%
“…Other methods use technique such as CAM or analogous techniques [15,19,28,81,85,111] as a form of weakly supervised saliency or localisation maps. Recent works have suggested that saliency methods can also be applied to self-supervised networks [13,35], e.g. for object colocalisation [13].…”
Section: Related Workmentioning
confidence: 99%
“…Differently, semantic information of objects is agnostic in self-supervised learning. Baek et al [23] proposed to utilize point symmetric transformation as the self-supervision signal to promote class-agnostic heatmap extraction in the object localization task. The aforementioned methods just utilize visual information to mine effective supervision.…”
Section: Object Localizationmentioning
confidence: 99%
“…Grad-CAM [31] and Grad-CAM++ [3] generalize CAM [56], so that CAMs can be obtained in any CNN-based classification models. The CAM technique derived from the classification network has been widely used for other weakly supervised visual tasks, such as localization [2,48], detection [39,43,55], segmentation [1,23,44].…”
Section: Related Work 21 Class Activation Mapmentioning
confidence: 99%
“…It is easily obtained by computing a weighted sum of the feature maps of the last convolutional layer. In fact, we can also obtain a class-agnostic activation map (CAAM [2]) by computing the sum of the feature maps directly, which indicates the spatial distribution of the embedded features. To describe our motivation visually, in Figure 1 we show some validation images misclassified by a pre-trained ResNet-50 [14] model with cross entropy loss on ImageNet [29].…”
Section: Introductionmentioning
confidence: 99%